Public policies for dialysis patients with bone mineral disease: Public policies for dialysis patients with bone mineral disease: literature review (Brazilian Journal of Health Research, 2024)
Introduction: With the aging of the population, the increase in Chronic Non-Communicable Diseases and the difficulty of controlling these diseases in the basic health network, chronic kidney disease is increasingly prevalent and is now considered a Public Health problem due to its exponential growth world level. Mineral and Bone Disorders are important complications of chronic kidney disease, associated with adverse outcomes, including increased mortality. The biggest challenge in the treatment of chronic kidney disease is the appropriate and multidisciplinary treatment of Bone Mineral Disease. Public health policies for coping with chronic kidney disease are recent and need many adjustments, and do not include a care network, and public services of specialized care for the monitoring of this serious complication of dialysis patients. Objective: To describe public health policies that contribute to coping with Bone Mineral Disease in dialysis patients. Method: Narrative review using descriptors in the Decs BVS and in the catalog of authorities of the National Library on “Public Health Policies” and “Bone Mineral Disease. Results/conclusion: chronological description of public policies in chronic kidney disease and its main complication, Bone Mineral Disease, highlighting the challenges and perspectives of coping with the disease in the current scenario in the state of Espírito Santo, Brazil.
Keywords: Health Policy; Chronic Kidney Disease-Mineral and Bone Disorder; Chronic Kidney Failure